The Effort to Teach PGSD Students in Developing Geometry Learning Method Based on Van Hiele’s Theory - Nugraheni, Wahyuningsih, Nursiwi (Elementary School Teacher, 2017)
The purposes of this study are 1). To describe the activities of lecturers in improving the PGSD Unnes students’ ability to design the learning of geometry based on Van Hiele’s theory. 2). To describe the activities of students in improving the ability to design the learning of geometry based on Van Hiele’s theory 3). To know the students’ learning outcomes in developing learning activity of elementary geometry by implementing Van Hiele’s theory on PGSD students UNNES. This research is a classroom action research conducted in two cycles and each cycle consists of two meetings. Each cycle consists of planning, execution, observation, and evaluation. The subjects of this study are lecturers of geometry and students who take geometry course. The technique in collecting data is using test and non-test techniques. The data analysis is done in quantitative and qualitative descriptive analysis. The result shows that all students can achieve mastery learning. It is suggested that a set of task bills so that prerequisites have been owned by the students. Structured tasks should be given to see the students’ ability.